Sistema de reprodução em populações naturais de Peltophorum dubium - Mori, Edson Seizo [UNESP]; Sebbenn, Alexandre Magno; Tambarussi, Evandro Vagner; Guries, Raymond Paul (Ipef-inst Pesquisas Estudos Florestais, 2013)
A Multi-locus mixed mating model and correlated mating model were used to analyze the mating system of four natural populations of Peltophorum dubium (Sprengel) Taubert from Western Sao Paulo State, Brazil. Open pollinated seeds were collected from 19 to 33 seed-trees per population and evaluated by allozyme electrophoresis analysis. Significant differences between pollen and ovule gene frequencies were detected in more than 50% of loci in each population, indicating deviations from random mating, probably due to correlated mating, self-fertilizations and mating among relatives. The comparison the fixation index estimated from seed trees ((F) over cap (m), ranged from 0.009 to 0.285) with their progenies ((F) over cap (p), ranged from 0.127 to 0.364) suggested selection against inbreeding between offspring of adult stages. The estimates of multi-locus outcrossing rate (t(m)) ranged from 0.557 to 0.924, indicating that the species has a mixed-mating system. Differences between multi-locus and single-locus outcrossing rate (t(m)-t(s))was positive and significantly different from zero for all populations, with values ranging from 0.092 to 0.111, suggesting mating among relatives within the populations, probably due to the presence of intra-population spatial genetic structure. The mean coefficient of co-ancestry (Theta) within progenies ranged from 0.147 to 0.251; confirming that the progenies are compounded by mixtures of different kinds of relatedness. The results are discussed from the view of genetic improvement and conservation of the species.
Mating system in natural populations of Peltophorum dubium
Keywords: Cana-fistula; co-ancestry; correlated mating; inbreeding; isozynnes; outcrossing rate